2011
DOI: 10.1080/15222055.2011.629946
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality in Tilapia Transport: From the Farm to the Retail Store

Abstract: Nile tilapia Oreochromis niloticus are routinely transported 1,200–1,400 km from Idaho to live markets in the greater Vancouver, British Columbia, area. Direct hauling mortality is typically very low, but significant economic losses occur during retail holding owing to a deterioration in physical appearance that results in fish that cannot be sold and their subsequent mortality. To address this problem, information was collected on hauling systems and protocols, holding systems and water management protocols, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…To maintain consistent dissolved oxygen levels at ≥5 mg L −1 , compressed oxygen was continuously supplied and not adjusted while fish were in buckets. This resulted in saturated dissolved oxygen levels similar to those reported during commercial transport (Colt, Momoda, Chitwood, Fornshell & Schreck ). Prior to the addition of fish to buckets, a water chemistry meter (HACH ® Model: HQ40d; HACH Company, Loveland, CO, USA) was used to measure pH (HACH ® PHC101 probe), temperature, dissolved oxygen (HACH ® LDO101 probe) and total ammonia nitrogen (TAN) (HACH ® IntelliCAL Ammonia probe ISENH3181) in tank water.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…To maintain consistent dissolved oxygen levels at ≥5 mg L −1 , compressed oxygen was continuously supplied and not adjusted while fish were in buckets. This resulted in saturated dissolved oxygen levels similar to those reported during commercial transport (Colt, Momoda, Chitwood, Fornshell & Schreck ). Prior to the addition of fish to buckets, a water chemistry meter (HACH ® Model: HQ40d; HACH Company, Loveland, CO, USA) was used to measure pH (HACH ® PHC101 probe), temperature, dissolved oxygen (HACH ® LDO101 probe) and total ammonia nitrogen (TAN) (HACH ® IntelliCAL Ammonia probe ISENH3181) in tank water.…”
Section: Methodssupporting
confidence: 78%
“…While tilapia have been shown to be tolerant of similar high TAN levels during live transport (Colt et al . ), the application of AQUI‐S ® 20E in buckets resulted in similar ammonia levels to untreated controls.…”
Section: Discussionmentioning
confidence: 74%
“…Consequently, there were low concentrations of toxic metabolites in the water, such as ammonia and H 2 S. However, Nile tilapia juveniles have grown surprisingly well on acidic organic-matter rich waters (pH < 6) in previous studies carried out in our laboratory (Nobre, Lima, & Magalhães, 2014;Rebouças, Lima, & Cavalcante, 2015;Silva, Santos Lima, Vale, & Carmo, 2013). Colt, Momoda, Chitwood, Fornshell, and Schreck (2011) have also found that O. niloticus could be transferred from pH 6 -7 to as low as pH 4.2 without problems. Due to the discrepancy between these results and those reported by El-Sherif and ElFeky (2009).…”
Section: Introductionmentioning
confidence: 75%
“…Nevertheless, the dissolved oxygen condition in the L and TL treatment was in optimum condition. The optimum dissolved oxygen to support the survival of Nile tilapia was ranged from 3-5.6 mg/L (Colt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%